(untitled) (Physical Education, Health and Social Sciences, 2026)
Pressure ulcers remain a significant and largely preventable patient safety concern, particularly in tertiary care settings where patients are at increased risk due to immobility and critical illness. Nurses play a central role in pressure ulcer prevention; however, variations in their knowledge and clinical practices can compromise care quality. This study aimed to evaluate nurses’ knowledge and practice regarding pressure ulcer prevention and to examine the relationship between these two variables in tertiary care hospitals in Bannu, Pakistan. A cross-sectional descriptive design was employed, and data were collected from 161 registered nurses using a structured and validated questionnaire assessing demographic characteristics, knowledge, and preventive practices. Data were analyzed using SPSS, applying descriptive statistics, reliability analysis, and appropriate non-parametric inferential tests due to non-normal data distribution. The findings revealed moderate levels of knowledge and practice among nurses, with acceptable reliability of the assessment tool. A statistically significant positive relationship was observed between knowledge and practice scores, indicating that higher knowledge levels were associated with better preventive practices. Training status and clinical experience were also found to influence knowledge and practice outcomes. Despite reasonable awareness of pressure ulcer prevention, gaps in consistent clinical implementation were evident. The study highlights the need for continuous professional training, standardized institutional protocols, and supportive work environments to bridge the knowledge–practice gap. Strengthening nurses’ competencies in pressure ulcer prevention can enhance patient safety, reduce healthcare costs, and improve the overall quality of nursing care in tertiary healthcare settings.